Characteristics of Patients With Congestive Heart Failure or Chronic Obstructive Pulmonary Disease Readmissions Within 30 Days Following an Acute Exacerbation. Issue 3 (July 2017) - Castillo, Austin; Edriss, Hawa; Selvan, Kavitha; Nugent, Kenneth
Abstract : Background: The Hospital Readmissions Reduction Program targets Medicare patients with congestive heart failure (CHF) and chronic obstructive pulmonary disease (COPD) and penalizes hospitals that have increased 30-day readmission rates for these patients. The main goals of this study were to determine the clinical explanations for readmissions within 30 days, to identify possible deficiencies in patient care, and to identify typical characteristics of patients who were readmitted to the hospital. Methods: The medical records department at University Medical Center in Lubbock, Texas, generated a list of patients with a primary discharge diagnosis of either acute exacerbation of CHF or an acute exacerbation of COPD who were readmitted within 30 days of discharge. Data collected from the electronic medical records included demographic information, clinical information, laboratory data, electrocardiographic information, echocardiographic results, and radiographic information for the index admission and readmission hospitalization. The indication for readmission was determined after review of all clinical data. Results: The final study cohorts included 58 admission-readmission events for acute exacerbations of CHF (47 patients) and 27 admission-readmission events for acute exacerbations of COPD (16 patients). Patients in both cohorts had significant comorbidity and frequent admissions during the 12 months prior to their index admissions. Patients with COPD had predominantly an emphysematous phenotype. Chest radiographs in patients with CHF showed cardiomegaly, pulmonary edema, and pleural effusions. Patients with CHF were discharged with suboptimal medication regimens. Referral to outpatient rehabilitation programs was low in both groups. Conclusions: Patients with acute exacerbations of COPD or CHF who require readmission within 30 days have complex comorbidity. They appear to have typical clinical profiles (emphysematous-type COPD patients and CHF patients with fluid overload), are frequently discharged with suboptimal medication regimens, and are not referred to outpatient rehabilitation. These patients had frequent hospitalizations prior to index hospitalizations. This information provides the basis for a focused review of patients admitted to the hospital to identify factors that might contribute to readmission.